Analysis of Public Interest Towards Purchasing Broiler Chicken Meat at The PTM Market (Modern Traditional Pendopo) Empat Lawang District - Rama Andora; Bagus Dimas Setiawan; Teguh Karyono (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze public interest in broiler chickens and examine the factors that influence it. public interest in purchasing broiler chickens at Modern Traditional Market (PTM) Pendopo. This study was conducted from October to November 2024 at the Modern Traditional Pendopo Market, Pendopo District, Empat Lawang Regency with a sample size of 46 people. Hypothesis testing used the SPSS version 23 software application with non-parametric statistical data testing in accordance with social science data. The results of the study showed There is influence significant between Work (X3), Education (X6) and Intensity of Social Activities (X7) on Purchase Interest (Y) of Chicken. Where simultaneously there is an influence between Price, Texture, Work, Income, Amount Member Family, Education, Intensity Social and Religious Activities with Purchase Interest.